TINJAUAN SANITASI RUMAKH MAKAN DI PANTAI GANDORIAH KOTA PARIAMAN - Layli, Rahmi; Silfeni, Silfeni; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research is aims to describe sanitation in the several restaurants which located in along Gandariah beach at the Pariaman city. It has two indicators in such kind of room which is consists of space for eat, drink, and some supporting facilities. The type of this research is descriptive text by using qualitative and quantitative approach. The data is conducting by doing interview, observation, documentation, and questionnaire. This research using purposive sampling technique. then the data analyzed by reducing, presenting the data, conclusions and the percentage of respondents score level. The result of research are the condition of floor is quite good, the wash basin is made in glass bottle which is very unique, the fresh and clean water is come from drill well, it has five restrooms but only one of them explains about who can use it, three restaurants have their own restroom and one of them does not have roof, and there is limited trash can based on quality even quantity. Thus, the category of restaurant sanitation is good. The room for eat or drink is good category (2970-3861) with score 17,6 and TCR 79,36%. The category of facility is good (2835-3685,5) with score 13,90 and TCR 66,20%.Key words: Restaurant sanitation, Gandoriah beach